Program Edukasi "Gerakan Masakan Sehat Bergizi untuk Balita" untuk Mengatasi Underweight pada Balita - Fadza, Muhamad Adli; Rakhman, Annisa Aulia; Romeil, Afaren Tabina Jaziilah; Sihombing, Feni Sopia; Shabiyya, Jenitra Diary Hukma; Putri, Ananda Luthfiah; Dianah, Rosyda (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Underweight one of the growing health issues commonly found in developing countries, including Indonesia. The prevalence of underweight among toddlers nationally is still quite high. The results of the SSGI 2024 recorded a figure of 17.1%. Therefore, GEMASITA was present in the form of educational outreach to mothers of toddlers in Cipelang Village. Objective: The purpose of this service was to increase the knowledge of mothers of toddlers in preparing nutritious meals  to prevent underweight status in toddlers through education using print media and audiovisual media. Method: This public service was conducted by lecturers and students from IPB University on October 18, 2025, at the Cipelang Village Office Hall in Bogor. The event was attended by 31 participants, 19 of them are mothers of toddlers. The implementation included a pre-survey and media preparation, a pre-test, education through lectures, discussions, and question-and-answer sessions, a live cooking session followed by a post-test to assess the increase in knowledge Result: The pre-post-test results showed an insignificant increase in the knowledge (5.83%) and attitudes (6.12%) of mothers of toddlers. The pre-test standard deviation (SD) was 2.03 and 2.29, while the post-test SD was 2.77 and 2.48. Conclusion: The GEMASITA program resulted in an insignificant increase in the knowledge and attitudes of mothers of toddlers (average 5%), with the distribution of results varying (some mothers increased, some remained the same, and others decreased).